2021
DOI: 10.3390/app11094171
|View full text |Cite
|
Sign up to set email alerts
|

Open-Air Cold Plasma Device Leads to Selective Tumor Cell Cytotoxicity

Abstract: The need for effective and safe therapies for cancer is growing as aging is modifying its epidemiology. Cold atmospheric plasma (CAP) has gained attention as a potential anti-tumor therapy. CAP is a gas with enough energy to ionize a significant fraction of its constituent particles, forming equal numbers of positive ions and electrons. Timely-resolved output voltage measurement, emission spectroscopy, and quantification of reactive species (RS) in plasma-activated media (PAM) were performed to characterize th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
16
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 15 publications
(20 citation statements)
references
References 78 publications
(77 reference statements)
2
16
1
Order By: Relevance
“…Our previous results have studied the effect of CAP exposure in metabolic activity and viability of MCF7 and HCC1806 cells [19]. By comparing the metabolic activity of several cell lines after plasma exposure, we observed that longer CAP exposures were required to reduce metabolic activity in breast cancer cells than most of the cells tested [19].…”
Section: Discussionmentioning
confidence: 88%
See 4 more Smart Citations
“…Our previous results have studied the effect of CAP exposure in metabolic activity and viability of MCF7 and HCC1806 cells [19]. By comparing the metabolic activity of several cell lines after plasma exposure, we observed that longer CAP exposures were required to reduce metabolic activity in breast cancer cells than most of the cells tested [19].…”
Section: Discussionmentioning
confidence: 88%
“…Our previous results have studied the effect of CAP exposure in metabolic activity and viability of MCF7 and HCC1806 cells [19]. By comparing the metabolic activity of several cell lines after plasma exposure, we observed that longer CAP exposures were required to reduce metabolic activity in breast cancer cells than most of the cells tested [19]. However, the effect of plasma treatment in the cells' viability differed between triplenegative (MCF7) and hormonal-receptor-positive (HCC1806) breast cancer cell lines.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations